REGISTER USED IN BIRD TRADING AT DEPOK MARKET, SOLO: A STUDY OF SOCIOLINGUISTICS - NFN Kurniawan (Sirok Bastra, 2013)
AbstractIn using language people not only use the standard language which is easy to understand but also use languagevariation which will show their identity. They use register in their communication process which is clearlyunderstood by a particular people. That is why, to make the communication fluent, people also need to know andunderstand register of particular field which they frequently use in their communication. In society, people usemany kinds of language varieties that describe the changes in situational factors, such as address, setting andtopics. Each occupational group or social group has the difference of specific vocabularies associated. Therefore,each group has a different register, for example in bird trading. Although there are many people who understandthe meaning of the registers, they usually do not know when or how the register used. For that reasons, the writeris interested in doing this research closely related to register in trading bird and hopes it can help the readers tofind out the solution of their problem in understanding the register.Keywords: register, sociolinguistics, bird trading, Depok SoloAbstrakDalam menggunakan bahasa, orang tidak hanya menggunakan bahasa standar yang mudah dimengerti, tetapi jugamenggunakan variasi bahasa yang akan menunjukkan identitas pemakainya. Penutur menggunakan registerdalam proses komunikasi yang dipahami oleh orang-orang tertentu. Oleh karena itu, untuk menciptakankomunikasi yang lancar, penutur juga harus mengetahui dan memahami daftar dari bidang tertentu yang seringmereka gunakan dalam komunikasi mereka. Dalam masyarakat, orang menggunakan berbagai ragam bahasa yangmenggambarkan perubahan dalam faktor-faktor situasional, seperti alamat, pengaturan dan topik. Setiapkelompok kerja atau kelompok sosial memiliki perbedaan kosakata tertentu yang terkait. Oleh karena itu, masingmasingkelompok memiliki daftar yang berbeda, misalnya dalam perdagangan burung. Meskipun ada banyakorang yang memahami arti dari register, mereka biasanya tidak tahu kapan atau bagaimana register digunakan.Untuk alasan itu, penulis tertarik untuk melakukan penelitian ini terkait erat dengan register di perdaganganburung dan berharap dapat membantu pembaca untuk mengetahui solusi dari masalah mereka dalam memahamiregister.